A questão do valor na linguagem para (o círculo de) Bakhtin - Dionísio, Mariléia Tenório (2010)
Tone, intonation, emotional-volitional tone, index of social value, expressiveness, accent, value-based positioning, value judgment, evaluation, assessment, point of view, and ideology are all notions related to the issue of value (i.e., axiology) within the framework of ideas of the Bakhtin Circle. Considering the studies that have been published based on the bakhtinian thought in Brazil to date, we can say that most of them deal with those concepts in one way or another (e.g., Faraco, Miotello, Sobral, Amorim, Souza e Tezza). Nonetheless, there is no particular study that focuses on the relationships between the conception of language and the questions of value. Thus, the aim of this dissertation is to find out the status of value within the bakhtinian concept of language in some of Bakhtin‘s oeuvres. The adopted methodology is also based on the Bahkitin´s concept of epistemology as our approach tries to establish dialogues between the original writings and the Brazilian authors that addressed the subject.